Influence of supplementary feeding on weight gain of ostrich chicks (Struthiocamelus, Linnaeus,1758) under farm conditions in Rupendehi, Nepal (Our Nature, 2025)
Ostrich (Struthiocamelus, Linnaeus, 1758) farming is an emerging enterprise in Nepal. Only one breeding farm was started in Nepal in 2008. The present study was conducted to examine the impact of supplementary diet on the weight gain of Ostrich. Formulation and preparation of feeds was done by direct involvement in the farm. A total eight unsexed Ostrich chicks were selected in the present study by feeding two types of diet. Farm feed (normal diet) and supplementary diet were given to the Ostrich chicks for about four months in 2018 to measure the weight gain. In this study,both feeds showed little weight gain, the mean weight gain of first 15 days of study on normal diets was 7.6±0.2309 kg and 10.9±0.0186 kg on supplementary diets and it was significantly greater (P